Progress in Immunotherapy Research and Multidimensional Data Analysis in Pediatric Cerebral Palsy Rehabilitation Integration of Chinese and Western medicine - Zhang, Maoxiang; Yang Yu; Krapivkin Alexey I.; Bukreeva E.A.; Sergeenko E.U. (Trends in Immunotherapy, 2025)
The study conducted multidimensional data analysis on clinical records of 1,586 children with cerebral palsy to investigate the therapeutic value of immunotherapy in cerebral palsy rehabilitation and the advantages of integrated traditional Chinese and Western medicine treatment. Using a multi-center, prospective cohort study design, a standardized data collection system was established, encompassing clinical baseline databases, treatment protocol records, and follow-up data collection. Baseline data analysis revealed significant heterogeneity among patients in clinical types, immune function, and Traditional Chinese Medicine (TCM) syndromes, with spastic type being the most common (52.46%) and immune function indicators generally below normal reference values. Patients were divided into four groups based on treatment protocols: modern rehabilitation therapy alone (Group A), modern rehabilitation combined with immunomodulation therapy (Group B), modern rehabilitation combined with TCM treatment (Group C), and modern rehabilitation combined with both immunomodulation and TCM treatment (Group D). After 12 months of treatment, comprehensive evaluation showed that Group D achieved a total effective rate of 91.86%, significantly higher than other groups; GMFM-88 scores improved by 24.78±5.89 points, with the most notable improvement in immune function indicators, particularly NK cell activity increasing from 12.43% to 18.45%. Multivariate analysis identified early diagnosis and treatment (≤2 years), normal baseline immune function, and standardized combination therapy as independent protective factors for favorable prognosis. Further research revealed that integrated Chinese and Western medicine treatment showed significant advantages in improving motor function, regulating immune status, and reducing adverse reactions, with the combination therapy group showing a 45.67% reduction in recurrence rate and achieving 91.23% parental satisfaction. Through multidimensional data analysis, this study confirms the significant value of immunotherapy while providing important evidence for optimizing cerebral palsy rehabilitation strategies and developing individualized treatment plans. Future research should focus on optimizing data analysis methods, innovating integrated Chinese-Western medicine models, developing intelligent diagnosis and treatment systems, and advancing multi-center collaborative research to further improve the overall level of cerebral palsy rehabilitation.